PELEMBAGAAN NILAI-NILAI INTI DI PT DARYA-VARIA LABORATORIA TBK - , Diani Savitri ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Starting from the aspirations of the top management team of Darya-Varia to promptly actualize its strategic vision, the top management realized the need of values as a standard of behavior for all the employees. The values that have been successfully formulated describes the prominent organizational culture in Darya- Varia and its two affiliates (Prafa and Medifarma), as well as it could play a role in directing the employeesâ behavior to achieve the vision. In order for the seven core values of âBERSATUâ to be understood, believed, and implemented consistently by all the employees in all the three companies, Darya-Varia has designed three phases to build a new culture (phase of hearing it, phase of believing it, and phase of living it). Phase of âliving itâ is the phase that the implementation of âBERSATUâ has become a routine action. It means that the institutionalization of values in Darya-Varia could be successful if it has reached the phase of living it. This research aims to evaluate the steps implemented by Darya-Varia in the process of formulating, embedding, and institutionalizing of âBERSATUâ core values, and also to identify the factors that obstruct and influence the success of the institutionalization. The research method used is the qualitative method, where the data collection was performed by studying the company's documentations, indepth interviews, and observations on some employees to see the implementation of âBERSATUâ values. From the analysis of the results, it can be known that the steps implemented to the process of embedding and institutionalizing of core values, have led Darya- Varia to pass through the phase of hearing it and the phase of believing it, but have not reached to the phase of living it, considering the core values of âBERSATUâ have not been consistently demonstrated by all employees. Institutionalization of values in Darya-Varia still requires a lengthy process, but the steps and the roadmap planned by Darya-Varia are already correct. The current values that have been seen consistently demonstrated by the employees and the leaders are the bayanihan spirit and the behaviour of caring, while the values that has not been seen to be demonstrated is ethos of openness. Some of the key success factors of this institutionalization are: the tools to embed and institutionalize the values, consistent communication/socialization, and role modeling by the leaders.